Marketing strategy with marketing intelligence to increase the market share of Indonesian Sharia Banks - Ranggasukma, Retus Aleksiva; Samputra, Palupi Lindiasari; Yoesgiantoro, Donny (Journal of Economic, Business & Accounting Research, 2025)
Background: With the potential market share as the country with the largest Muslim population in the world, the existence of Indonesian Sharia Bank/Bank Syariah Indonesia (BSI) in Indonesia has indeed increased the development of Islamic banking, but has not been able to keep up with the prevalence of conventional bank market share so that both external and internal marketing strategies are needed with the utilization of marketing intelligence. This study aims to identify the characteristics of BSI customers by analyzing processes and performance, including comparing strengths and weaknesses with conventional banks so as to obtain marketing strategies to increase BSI market share. Methods This research is descriptive with a qualitative approach to the data obtained from interviews, documentation, and analysis of research subjects. Findings: The results show that the characteristics of BSI customers are young urban people with higher education and middle to upper economic levels. In BSI's marketing process and performance, the utilization of marketing intelligence is likened to an intelligence cycle, although it is not optimal because it still depends on data from external research companies. BSI has also not optimally implemented Blue Ocean Strategy that utilizes product uniqueness and tends to conduct Red Ocean Strategy to dominate the conventional bank market in increasing market share. Conclusion: The recommended marketing strategies include utilizing product uniqueness to create new markets, developing user-friendly transaction technology and digital platforms, strengthening positioning and brand awareness through Islamic ecosystem-based marketing, and intensifying digital marketing as a brand presence that increases public trust. Novelty/Originality of this article: The novelty aspect refers to the new or innovative elements in a research study that distinguish it from previous work. It includes unique contributions, new methods, or findings that have not been explored before in the field.